2021
DOI: 10.1093/pubmed/fdab037
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities between the impact of the first and the second COVID-19-lockdown on mental health and safety behaviour in Germany

Abstract: Background Governmental restrictions of daily life are key elements in reducing the transmission of COVID-19, but they have also put a strain on people’s mental health. Preventive policies differ all over the world as well as over different periods of time, and depend mostly on current infection rates. In Germany, there were two periods of restraint of varying severity, during which the government used different combinations of containment and mitigation measures to protect risk groups and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 16 publications
(7 reference statements)
5
62
0
3
Order By: Relevance
“… Richter et al (2021) highlighted that mental health care utilization indicators did not suggest an increased demand during the first lockdown phase, which is in line with our results. Also, Moradian et al (2021) demonstrated the impact of COVID-19 on patients mental health in Germany using longitudinal data, revealing a prolonged negative impact on people's mental health in Germany despite the fact that less intensive restrictions were introduced during the second lockdown compared to the first, which may be interpreted as pandemic fatigue. This is in line with this analysis' results, demonstrating that anxiety disorders were documented more often the more prolonged the COVID-19 pandemic and its imposed measures last.…”
Section: Discussionmentioning
confidence: 99%
“… Richter et al (2021) highlighted that mental health care utilization indicators did not suggest an increased demand during the first lockdown phase, which is in line with our results. Also, Moradian et al (2021) demonstrated the impact of COVID-19 on patients mental health in Germany using longitudinal data, revealing a prolonged negative impact on people's mental health in Germany despite the fact that less intensive restrictions were introduced during the second lockdown compared to the first, which may be interpreted as pandemic fatigue. This is in line with this analysis' results, demonstrating that anxiety disorders were documented more often the more prolonged the COVID-19 pandemic and its imposed measures last.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries, including the Netherlands experienced multiple waves of COVID-19 infections and a prolonged lockdown. Comparing the effect of the first and the second lockdown on mental health, increased depressive symptoms and a higher psychological burden in the second lockdown were reported in Germany and Austria, although the restrictions were less strict compared to the first lockdown (Moradian et al 2021 ; Dale et al 2021 ). Therefore the results for optimism and meaning in life might also be different further into the pandemic or the effects might change over time.…”
Section: Discussionmentioning
confidence: 99%
“…An Austrian study showed lower wellbeing and higher stress levels during the rst COVID-19-related lockdown, when infection rates were high, than six months later, when infection rates were low [20]. A study conducted in Germany also found a signi cant decline in wellbeing from the rst to the second wave [21]. The authors also observed a decrease in safety behavior and, therefore, interpreted the ndings as pandemic fatigue (rather than increased own concern).…”
Section: Discussionmentioning
confidence: 97%